HOXA5 Is Recognized as a Prognostic-Related Biomarker and Promotes Glioma Progression Through Affecting Cell Cycle - Ding, Fengqin; Chen, Ping; Bie, Pengfei; Piao, Wenhua; Cheng, Quan (Frontiers in Oncology, 2021)
Glioma is malignant tumor derives from glial cells in the central nervous system. High grade glioma shows aggressive growth pattern, and conventional treatments such as surgical removal and chemo-radiotherapy archive limitation in the interference of this process. In this work, HOXA5, from the HOX family, was identified as glioma cells proliferation associated factor by investigating its feature in the TCGA and CGGA dataset. High HOXA5 expression samples contain unfavorable clinical features of glioma, including IDH wild type, un-methylated MGMT status, non-codel 1p19q status, malignant molecular subtype. Survival analysis indicates high HOXA5 expression samples are associated with worse clinical outcome. The CNVs and SNPs profile difference further confirmed the enrichment of glioma aggressive related biomarkers. In the meantime, the activation of DNA damage repair related pathways and TP53 related pathways is also related to HOXA5 expression. In cell line U87MG and U251, by interfering HOXA5 expression significantly inhibits glioma progression and apoptosis; and cell cycle is arrested at the G2/M phase. Collectively, increased HOXA5 expression can promote glioma progression via affecting glioma cells proliferation.